The Cow in the Room: Public Knowledge of the Links between Dietary Choices and Health and Environmental Impacts - Andrew W Joyce; Sarah Dixon; Jude Comfort; Jonathan Hallett (SAGE Publishing, 2008)
Issue Addressed This paper describes results of a survey comparing people's knowledge of health and environmental impacts of dietary choices. Dietary choice is one of the key ways in which individuals can reduce their environmental impact in relation to water use and greenhouse gas emissions but this may not be widely known amongst the public due to limited press coverage. Methods A street intercept survey was conducted asking open ended questions on how people can help the environment, maintain or improve health and basic demographics. The sample size was 107 with a refusal rate of 51%. Results Only 3.2% of the sample made a link between dietary choice and environmental impact whereas 85.6% of the sample referred to dietary choice in relation to personal health. Transport options and keeping active were popular responses to both health and environmental categories. Conclusions It seems that very few people are aware that the livestock sector is the second largest contributor to equivalent greenhouse gas emissions and one of the largest users of fresh water. Reduction in red meat consumption could have both important positive health and environmental impacts.